Three “R’s” for mine closure – responsibilities, regulations and results - Jones, h (Mine Closure 2011: Proceedings of the Sixth International Conference on Mine Closure, 2011)
The paper outlines an evolution of attitudes of governments and the mining industry to the concept of sustainable development with particular reference to mine closure. It considers the role professional associations have in promoting responsible attitudes to environmental management and mine closure. Focusing on the development of mine waste landforms the author briefly outlines the drivers of regulations and considers the process of regulation drafting together with the role of guidelines as de facto regulations. The paper then outlines the “prescriptive” and “enabling” approaches to legislation and discusses how they can impact on setting and attaining mine closure objectives. The application of regulations and the requirement of resources including skilled and experienced regulators is discussed together with the responsibilities of government should its regulations increase, rather than reduce environmental harm at closure. The concept of environmental compliance is briefly discussed including the potential technology restricting aspects of strict compliance with regulations. Does this promote a lowest common denominator approach to mine closure? With particular reference to the closure requirements of waste dumps and tailings structures the author gives illustrations of good and less than good examples of what regulations and industry performance have so far achieved. The time frame within which closure objectives attainment can be evaluated is discussed, highlighting the different time frames required to assess geomorphological and biological post closure performance at a mine. The site specific nature of mines means that one approach to waste landforms cannot fit all situations and the fairness of having a solution acceptable in one operation, but not in another is considered. The author concludes by outlining ways in which responsibilities and regulations could work together to improve the mine closure performance of our industry and demonstrate to the broader community that the term “sustainable development” is not an oxymoron when applied to the mining industry.